The Illegal Cigarette Underground Economy in Indonesia: A Threat to National Economic Security from an Intelligence Perspective - Atmana, Cahya Tri; Sunny, Amril Gaffar; Widyarsih, A. Victoria Rahajeng (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
The illegal cigarette underground economy erodes state revenues, distorts the market, and threatens national economic stability through the practice of cigarette production and distribution by avoiding excise/tax levies and regulations. This study aims to analyze the threat of these illegal economic practices from an intelligence perspective. This research focuses on identifying causal factors, modes of practice, and their impact on national economic security, as well as intelligence analysis to formulate countermeasures. The research method uses descriptive qualitative through interviews, observations, and literature studies. The findings revealed five causal source factors, seven modes of practice, and three harmful impacts. Hank Prunckun and Robert Ring's threat assessment model places the underground economy practice of illegal cigarettes as a serious/high level threat. Intelligence analysis detected a potential state loss due to illegal cigarettes of Rp18.46 trillion in 2023, the level of cigarette consumption of the population that has not fallen, and a depressed legal cigarette industry, which can threaten the stability of the state budget and national development. Strengthening inter-agency collaboration and synergy, enhancing the role of customs and excise intelligence, community mobilization, and appropriate excise tariff policies are needed in an effort to confront and tackle that illegal practice.